(untitled) (Journal of Hama University, 2020)
The aim of this experiment was to study the effect of unilateral castration in compensatory changes on the remaining testis in mature dogs. The experiment was conducted on 6 male domestic dogs between 2-4 years of age. The reproductive season was taken into consideration, The dogs were divided into two groups, the group of dogs within the reproductive season and the group of dogs outside the reproductive season. The first testis was removed and after 120 days the remaining testis was removed. The histological examination was performed using the Median Compeer Method to compare using (Sign-test). The results showed no significant differences (P>0.05) in the values ​​examined in the testis in both experimental groups for histological changes (Tubular diameter, Thickness of germinal epithelium, Area of tubular epithelium). According Histological findings, adult dogs do not undergo compensatory changes in the remaining testis within 120 days after unilateral castration.